DIAGNOSTIC MARKERS IN ACUTE APPENDICITIS: A SYSTEMATIC REVIEW - Hekmatyar, Mohamad (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Appendicitis is the most common emergency case of abdominal surgery and requires immediate surgical intervention to avoid serious complications. If appendicitis is treated late, it will increase patient morbidity and mortality. Despite the relatively high incidence of needless appendectomies, ranging from 20% to 30%, such occurrences are deemed tolerable given the substantial reliability of beneficial outcomes. The aim: This article showed diagnostic markers in acute appendicitis. Methods: This study demonstrated compliance with all requirements by comparing itself to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 standards. Therefore, the experts were able to ensure that the study was as current as feasible. For this search strategy, publications published between 2013 and 2023 were considered. Several online reference sources, including Pubmed and SagePub, were utilized for this purpose. It was determined not to consider review pieces, previously published works, or works that were only partially completed. Result: The PubMed database yielded a total of 87 articles in response to our search query, while the search conducted on SagePub resulted in 69 articles. The search conducted for the last year of 2013 resulted in a total of 29 articles found in PubMed and 31 papers found in SagePub. Ultimately, a comprehensive compilation of 22 papers was achieved, with 15 sourced from PubMed and an additional seven obtained via SagePub. We incorporated seven studies that satisfied the established criteria. Conclusion: Study shows that a shift in pain from the epigastrium to the Mc Burney point and heel drop test is a sign of appendicitis based on physical examination. Examination of white blood cells and CRP can be other reliable markers to confirm acute appendicitis.